Expanding Power or Constitutional Violation? The DPR’s Authority to Evaluate State Officials under Checks and Balances - Haikal Wisnu Saputra; Daksh Daksh (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to examine the Rules of Procedure of the Indonesian House of Representatives (DPR) concerning the authority to evaluate state officials within the framework of the checks-and-balances principle. This research employs a normative legal method using statutory and conceptual approaches. The primary focus is the legal basis for the DPR’s evaluative authority viewed through the existing constitutional principles of checks and balances. The findings indicate that the legal basis for the DPR’s authority to evaluate state officials creates legal uncertainty, thereby generating the potential for abuse of power and inconsistency with the checks-and-balances model embodied in the 1945 Constitution of the Republic of Indonesia (UUD 1945). Under Article 228A of the DPR Rules of Procedure of 2025, the DPR is permitted to conduct periodic evaluations of candidates who have been confirmed in a plenary session. Such regulation grants an authority that may threaten the independence of state institutions and rests on a weak legal foundation, as it does not fall within the recognized hierarchy of legislation and exceeds the DPR’s internal regulatory scope. Moreover, this norm poses risks to the balance among branches of state power, endangers the independence of public officials, and creates potential horizontal conflicts and legal uncertainty.